Podmiototwórczy potencjał intersubiektywności międzygatunkowej - Gzyra, Dariusz (Zoophilologica. Polish Journal of Animal Studies, 2017)
Intersubjectivity, understood as a relationship between different perspectives, that creates a common space, accessible to more than one cognizing subject, is the basic trait of our presence in the world. The realization of our capability potential for intersubjective relations is related to the realization of a similar potential of the other subject of such relationships. We recognize the subjectivity of others through the reference to ourselves – out of necessity. This process is connected with the recognition of similarities and differences. In the article I am analyzing the nature of this process and the risks associated with possible underestimation and overestimation of the value of the other. The principle of seeking sufficient similarity apparently results in the automatic exclusion of a certain scope of dissimilarity – for example, of what is too different for the creation of subjective, intersubjective relations. I am trying to show that the recognition of the dissimilarities of the others does not have to involve their devaluation. On the contrary, it presents a challenge to the ethical imagination and is an indispensable component of intersubjectivity. I am pointing out that effective interspecific communication, which takes into account the importance of the affective component and the meeting of the diverse experiencing corporeality, is also an important aspect of the described relationships. I am also pointing out that the question about the subjectivity occurring in relationships is also an ethical and political problem of great importance.